Utilização de fibroína de seda para imobilização de beta-amilóide para aplicação em imunossensores - Gonçalves, João Marcos [UNESP] (2015)
Silk fibroin (SF) and amyloid-β with 40 aminoacids (Aβ40) layer-by-layer (LbL) films for optical and electrochemical imunosensing applications were investigated. The growth of this films was confirmed by cyclic voltammetry (VC), observing changes in the voltammogram area and ultraviolet-visible region spectroscopy (UV-vis), observing increasing absorbance in 230 nm. The complete covering of an carbon electrode was verified using potassium ferrocyanide and ferricyanide in VC. There was distortion of the voltammograms with increasing adsorption time for the SF, and with 30 minutes was observed the maximum distortion, and therefore maximum electrode coverage. A conformation change of the peptide Aβ40 in the film was also observed using circular dichroism (CD). In the solution the peptide presented an characteristic spectrum of α-helix structure and in the film was observed the predominance of β-sheet structure. For the optical immunosensor an YVO4:Eu3+ nanoparticle suspension to monitor the europium emission. The LbL films had an excitation maximum centered in 270 nm and the europium emission in 619 nm, it was also observed an emission centered in 300 nm attributed to the SF and Aβ40. After the addition of antibodies, it was observed an increase in Eu3+ emission and a decrease of protein emission, associated with an energy transfer from SF/Aβ40 to the Eu3+. In the optical detection this effect was observer in the absence of peptide, therefore non-specific interactions between antibodies and the substrate. The electrochemical detection of the antibodies solution was performed with VC and were observed changes in voltammograms: an increase of current in positive potentials and an increase in voltammogram area. Both had a linear response in the 0 through 10 ng.mL-1 range and this response was observed only in the presence of the Aβ40.